ANALYSIS OF THE INFLUENCE OF DIGITAL PAYMENT SYSTEMS ON THE SALES LEVEL OF MSMEs AT THE MEDAN CITY MARKET CENTER - Mahlia Putri Hasibuan; Muhammad Syukri Albani Nasution; Muhammad Irwan Padli Nasution (International Journal of Cultural and Social Science, 2025)
This study investigates the effect of digital payment systems on the sales level of MSMEs in the Medan City Market Center using a qualitative phenomenological approach. The research focused on fashion-sector MSMEs that had been operating for more than three years and had experience using digital payments such as bank transfers, DANA, and OVO in their business activities. Data was obtained through observation and in-depth interviews with purposively selected informants. The results showed that the implementation of digital payment systems contributed to increased transaction convenience, expanded consumer access, and operational effectiveness, which generally had a positive impact on sales growth. However, obstacles were also identified, including limited digital literacy, consumer preference for cash payments, and MSME concerns about transaction security. This research emphasizes the importance of digitalization for MSMEs to adapt to the current of modern economic transformation, while also considering social, cultural, and technological readiness aspects in traditional market environments.